Community Based Screening for Depression in Diabetes Mellitus in Urban Areas of Thiruvallur District. A Cross Sectional-Analytical Study - kumar, G. Nirmal; Kumar, Praveen; Kumar, Buvnesh; Gokul, Gokul (Journal of Neonatal Surgery, 2025)
Type 2 diabetes and depression are serious health issues in our society. Chronic diseases like diabetes may stress people and impact pathophysiologic systems and mood. This may cause despair and a poor T2DM prognosis. T2DM patients with depression are at risk for heart disease, stroke, and death. Depressive symptoms are not screened for, hence depression is underdiagnosed in diabetes patients despite its increased incidence and management burden. This research estimated the frequency of depression in T2DM patients in Thiruvallur District and examined its relationship to glycaemic management and other risk variables. This descriptive cross-sectional research included 271 T2DM patients from Urban Health Training Centre (UHTC), Thirumazhisai, our urban field practice region. The trial ran from July to August 2024. The nine-item “Patient Health Questionnaire-9” was used to screen for depression and monitor fasting and postprandial blood sugar levels. 46.5% of 271 T2DM patients were women and 53.5% were men. The average participation age was 55.12. 75.6 percent of research participants had FBS ≥ 125 mg/dl. Among the 69.3% with depression, 44% had mild, 14% moderate, 8% moderately severe, and 4% severe. Fasting blood glucose, family history, complications, diabetes duration, and exercise were substantially linked with depression. This research reveals that depression is common in T2DM patients and is linked to poor prognosis, as seen by poor FBS and PPBS and diabetes complications. Screening and counselling for depression in T2DM patients are necessary for optimal management and therapy.